Investigating the relationship between changes in collagen fiber orientation during skin aging and collagen/water interactions by polarized-FTIR microimaging1. Issue 18 (21st September 2015) - Eklouh-Molinier, Christophe; Happillon, Teddy; Bouland, Nicole; Fichel, Caroline; Diébold, Marie-Danièle; Angiboust, Jean-François; Manfait, Michel; Brassart-Pasco, Sylvie; Piot, Olivier
<x xml:space="preserve">Abstract</x> Polarized-FTIR imaging highlights the importance of bound water in collagen fiber orientation changes during skin aging.